Smart Interconnection Method for Integrating Two Microgrids - Ahmad S.; Awalin L.J.; Ferdous Riya J.; Billah A.G.M.M.; Ahmed T.; Mekhilef S.; Mokhlis H.; Seyedmahmoudian M.; Stojcevski A. (Institute of Electrical and Electronics Engineers Inc., 2024)
The resilience and dependability of the power distribution system have been increased by interconnecting several microgrids to create interconnected microgrids. While interconnecting the microgrids, there is ambiguity regarding balanced power sharing across several microgrids. The power mismatch between the generating capacity of distributed energy sources and the load demands of all the microgrids is taken into consideration in this study, a smart interconnection method (SIM) is proposed for tying together two microgrids that are interconnected to the utility grid. The advantage of the suggested technique is the easy, real-time construction of circuitry that is adjustable and simple. To evaluate the effectiveness of the interconnection approach, real-time simulations are carried out using a real-time digital simulator (RTDS). The outcomes of the simulation have confirmed the effectiveness of the proposed smart interconnecting method for connecting two microgrids during grid-connected mode. 2023 IEEE.